Temporary land use permit in Selangor: an overview of land policies and practice in the district of Petaling, Malaysia / Liyana Zainudin, Zaharah Mohd Yusof and Jaiya Abu - Zainudin, Liyana; Mohd Yusof, Zaharah; Abu, Jaiya (UiTM Press, 2023)
As the leading district in Malaysia, the district of Petaling (in the state of Selangor) has embarked on multiple development strategies towards materializing urban growth and producing main cities. The state's structural plan has selected Petaling to champion urban growth where its three local authorities are required to develop their lands for other than agricultural use. This study will look into how the district implements the use of special temporary permits in regard to temporary land use through specific federal and state government's circulars. Qualitative data analysis through Acts and documents i.e. circulars, local plans and town plans produced by the Department of Director General of Lands and Mines and the Selangor Land and Mines Office were analysed, compared and discussed in regards to achieving urban growth. Findings show that the circulars are not feasible within the context of Petaling and it is recommended that a further study to introduce a new permit for temporary land use for residential, industrial and commercial lands be considered, alongside a flexible policy that complements urban growth.